A comparison of repaired, remanufactured and new compressors used in Western Australian small- and medium-sized enterprises in terms of global warming - Wahidul K. Biswas; Victor Duong; Peter Frey; Mohammad Islam (Journal of Remanufacturing, 2013)
Repaired compressors are compared with remanufactured and new compressors in terms of economic and environmental benefits. A detailed life cycle assessment has been carried out for compressors under three manufacturing strategies: repaired, remanufactured and new equipment. The life cycle assessment of the global warming potential of repaired compressors varies from 4.38 to 119 kg carbon dioxide equivalent (CO2-e), depending on the type of components replaced. While greenhouse gas emissions from the remanufactured compressors (110 to 168 kg CO2-e) are relatively higher than those from the repaired ones (4.4 to 119 kg CO2-e), a new compressor has been found to produce a larger amount of greenhouse gas emissions (1,590 kg CO2-e) compared to both repaired and remanufactured compressors. Repairing failed compressors has been found to offer end users both dollar and carbon savings in contrast to remanufactured and new compressors. The research also found that extended lifetime is more important than the manufacturing processes in terms of greenhouse gas emissions. Since a remanufactured compressor offers a longer life than a repaired compressor, the replacement of the latter with the former can avoid 33% to 66% of the greenhouse gas emissions associated with a new compressor production with a lifetime of 15 to 25 years.
Keywords: 650; end-of-life product; life cycle assessment; global warming; Maschinenteile; Produktlebenszyklus; Produkt-Recycling; Klimawandel; Western Australia (Staat)